Aspects Regarding Ethics and Integrity in Romanian Scientific Research - Lupu, Nicolae; Bîgu, Dragoş (Amfiteatru economic, 2022)
In order to genuinely perform its function in society, scientific research in general and socialresearch in particular must comply with ethical standards, which guarantee that the researchresults are correct, in accordance with the needs of society, do not harm research subjects andthe community as a whole, and do not violate the rights of any research participant. Integritycodes and research ethics committees play a central role in ensuring the compliance ofscientific practice with ethical standards. In order to highlight the degree of compliance ofresearch activities with ethical norms, as well as specific problems, we will resort to themethod of content analysis of complaints regarding potential violations of ethical norms,reports and decisions from recent years of the National Council of Ethics of ScientificResearch, Technology Development and Innovation, as well as the National Council forAttesting University Titles, Diplomas and Certificates, attached to the relevant ministries inRomania.